Colossal Magnetoresistance without Mixed Valence in a Layered Phosphide Crystal. Issue 10 (29th January 2021) - Wang, Zhi‐Cheng; Rogers, Jared D.; Yao, Xiaohan; Nichols, Renee; Atay, Kemal; Xu, Bochao; Franklin, Jacob; Sochnikov, Ilya; Ryan, Philip J.; Haskel, Daniel; Tafti, Fazel
Abstract: Materials with strong magnetoresistive responses are the backbone of spintronic technology, magnetic sensors, and hard drives. Among them, manganese oxides with a mixed valence and a cubic perovskite structure stand out due to their colossal magnetoresistance (CMR). A double exchange interaction underlies the CMR in manganates, whereby charge transport is enhanced when the spins on neighboring Mn 3+ and Mn 4+ ions are parallel. Prior efforts to find different materials or mechanisms for CMR resulted in a much smaller effect. Here an enormous CMR at low temperatures in EuCd2 P2 without manganese, oxygen, mixed valence, or cubic perovskite structure is shown. EuCd2 P2 has a layered trigonal lattice and exhibits antiferromagnetic ordering at 11 K. The magnitude of CMR (10 4 %) in as‐grown crystals of EuCd2 P2 rivals the magnitude in optimized thin films of manganates. The magnetization, transport, and synchrotron X‐ray data suggest that strong magnetic fluctuations are responsible for this phenomenon. The realization of CMR at low temperatures without heterovalency leads to a new regime for materials and technologies related to antiferromagnetic spintronics. Abstract : A change of paradigm in a technologically important phenomenon, the colossal magnetoresistance (CMR), is introduced. Previously, it was believed that the CMR required ferromagnetic ordering and a structural distortion. EuCd2 P2 has antiferromagnetic ordering and does not have a structural distortion or mixed valence, yet it exhibits the largest CMR known in a single crystal.